2022
DOI: 10.1371/journal.pone.0266482
|View full text |Cite
|
Sign up to set email alerts
|

Residual effect of defeated stripe rust resistance genes/QTLs in bread wheat against prevalent pathotypes of Puccinia striiformis f. sp. tritici

Abstract: The periodic breakdowns of stripe rust resistance due to emergence of new virulent and more aggressive pathotypes of Puccinia striiformis f. sp. tritici have resulted in severe epidemics in India. This necessitates the search for new and more durable resistance sources against stripe rust. The three bread wheat cultivars PBW 343 (carries Yr9 and Yr27), PBW 621 (carries Yr17) and HD 2967 (gene not known) were highly popular among the farmers after their release in 2011. But presently all three cultivars are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…13 Non-hematology medical research and biology studies used the same application to measure irregular areas in images. [14][15][16][17] In preliminary studies using this application, we demonstrated that measurements of percentage areas of segments under a computer-generated normal distribution curve were accurate and precise. 18 To explore potential hematology research applicability of this method, we measured areas of archived AHA RBC volume histogram images that correspond to microcytes and macrocytes in women with previously untreated iron-deficiency anemia (IDA) and women with previously untreated hemochromatosis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…13 Non-hematology medical research and biology studies used the same application to measure irregular areas in images. [14][15][16][17] In preliminary studies using this application, we demonstrated that measurements of percentage areas of segments under a computer-generated normal distribution curve were accurate and precise. 18 To explore potential hematology research applicability of this method, we measured areas of archived AHA RBC volume histogram images that correspond to microcytes and macrocytes in women with previously untreated iron-deficiency anemia (IDA) and women with previously untreated hemochromatosis.…”
Section: Introductionmentioning
confidence: 95%
“…We developed a method to quantify microcyte and macrocyte percentages in archived AHA RBC volume histogram images using an on‐line application of Gauss' area formula, also known as the “shoelace” formula 13 . Non‐hematology medical research and biology studies used the same application to measure irregular areas in images 14–17 . In preliminary studies using this application, we demonstrated that measurements of percentage areas of segments under a computer‐generated normal distribution curve were accurate and precise 18 …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, 86 officially designated stripe rust resistance genes, 71 temporarily designated genes and 363 quantitative trait loci (QTLs) with different names have been reported in wheat. The 86 officially designated stripe rust resistance genes include 22 APR genes and 6 HTAP resistance genes [ 5 , 6 ]. Nine Yr genes have been cloned.…”
Section: Introductionmentioning
confidence: 99%